2018
DOI: 10.1007/s12035-017-0848-0
|View full text |Cite
|
Sign up to set email alerts
|

In Thai Nationals, the ApoE4 Allele Affects Multiple Domains of Neuropsychological, Biobehavioral, and Social Functioning Thereby Contributing to Alzheimer’s Disorder, while the ApoE3 Allele Protects Against Neuropsychiatric Symptoms and Psychosocial Deficits

Abstract: The apolipoprotein E epsilon 4 (ApoE4) allele is the strongest genetic risk factor for Alzheimer's disorder (AD) and is associated with semantic and episodic memory deficits. The aim of this study was to examine the associations between ApoE alleles (E2, E3, E4) and genotypes and neuropsychological tests, behavioral functions, and dementia symptoms as assessed using Consortium to Establish a Registry for Alzheimer's Disease (CERAD). This study included 60 patients with Alzheimer's disorder (AD), 60 with mild c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Some recent studies [300,301] show that the default-mode network in APOE 4 subjects differs from non- APOE 4 in a way that APOE 4 seems to establish the functional communications across different brain regions (connectomics), which could predispose to some cognitive disadvantage across the entire lifespan. Moreover, some investigations pointed out that there is indeed an association between cognition measurements and personality traits [302,303]. If these links are also based, influenced, or modulated by a specific genotype, such APOE 4 vs. APOE 2 is under investigation.…”
Section: Box 1 Possible Apoe-linked Biological Traits Associated Witmentioning
confidence: 99%
“…Some recent studies [300,301] show that the default-mode network in APOE 4 subjects differs from non- APOE 4 in a way that APOE 4 seems to establish the functional communications across different brain regions (connectomics), which could predispose to some cognitive disadvantage across the entire lifespan. Moreover, some investigations pointed out that there is indeed an association between cognition measurements and personality traits [302,303]. If these links are also based, influenced, or modulated by a specific genotype, such APOE 4 vs. APOE 2 is under investigation.…”
Section: Box 1 Possible Apoe-linked Biological Traits Associated Witmentioning
confidence: 99%
“…Also, APOE ε4 carriers have been demonstrated to experience an earlier onset of memory decline and to have greater rates of disease progression than non-APOE ε4 carriers (Ungar et al, 2014 ). Neuropsychological studies have revealed that APOE ε4 has a significant effect on general cognitive function (Tangwongchai et al, 2018 ), especially episodic memory (Rajah et al, 2017 ). Neuropathological studies in human and animal models have proved that APOE ε4 has a physical interaction with Aβ, which has a strong influence on memory deficit in probable preclinical AD (Holtzman et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The early phases of AD are characterized by a gradual decline in neurocognitive functions including impairments in episodic and semantic memory and word fluency [5,6]. In the later stages of AD, patients suffer from deficits in memory, language and naming, orientation, executive functions, perceptual-motor functions, attention, and social skills including communication and judgement [6,7]. At that stage, difficulties to perform activities of daily living (ADL) and neuropsychiatric symptoms, such as behavioral dysregulation, irritability and aggression, inertia, and depressive, vegetative and psychotic symptoms, may be evident [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the later stages of AD, patients suffer from deficits in memory, language and naming, orientation, executive functions, perceptual-motor functions, attention, and social skills including communication and judgement [6,7]. At that stage, difficulties to perform activities of daily living (ADL) and neuropsychiatric symptoms, such as behavioral dysregulation, irritability and aggression, inertia, and depressive, vegetative and psychotic symptoms, may be evident [7]. The pathophysiology of AD comprises neuroinflammation with astrogliosis, neurofibrillary tangles, accumulation of amyloid plaques, dystrophic neurites with tau protein, and synaptic, neuronal and neuropil loss [2,3,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation